Application of ion beam analysis for the characterization of SiC- and DLC-thin films - Noli, F.; Misaelides, P.; Kokkoris, M.; Riviere, J. P. (HNPS Advances in Nuclear Physics, 2020)
Three series of protective coatings (thickness ca. 200-300 nm) were prepared on the surface of Ti-Al-V alloy (TA6V): silicon carbide (SiC) films produced by ion sputtering (I), silicon carbide films and subjected to Dynamic Ion Mixing (DIM) during the deposition procedure (II) and Diamond Like Carbon (DLC) films produced by ion beam deposition (III). The chemical composition (Si, C and O) of the films was determined using ion beam analysis techniques. The silicon, carbon and oxygen depth distribution was determined by proton Rutherford backscattering spectrometry (p-RBS) and using the resonances at 4.265 and 3.035 MeV of the 12C(α,α)12C and 16O(α,α)16O interactions respectively. The ratio of Si:C was found to be close to the stoichiometric one. The corrosion resistance of the coated samples was tested under strong aggressive conditions (5M HCl at 50 oC). The investigation following the corrosion attack showed that the thickness of the films remained practically unchanged. Only slight diffusion and dissolution effects were observed indicating the good quality of the produced thin films.